Comparison of effects between core stability training and sports massage therapy among elite weightlifters with chronic non-specific low back pain: A randomized cross-over study - Joseph, L. H.; Hancharoenkul, B.; Sitilertpisan, P.; Pirunsan, U.; Paungmali, A. (Asian Journal of Sports Medicine, 2018)
Background: Lumbopelvic stability training (LPST) and massage therapy are common therapies used for pain reduction and management of low back pain. However, the effects of LPST and sports massage therapy (SMT) for management of chronic non-specific low back pain (CLBP) among elite weightlifters have never been studied before.